Professional development of high school geography teachers’ with special reference to profession perception and profession commitment - K. Mohanasundram, S.Tamilenthi* and (Journal of Experimental Sciences, 2011)
The present investigation is intended to study the profession development of geography teachers high schools from perception of the class room teacher and how far the professional development is enabled to the students for better of their education. The scale of profession perception and profession commitment is constructed. Samples from 444 high schools geography teachers with normative survey and purposive sampling method. Statistical techniques were applied to draw the result. The Personal variables were studied with respect to locality of the institution, medium of teaching and type of the management of Geography teacher is compared. The significant difference is found in medium of teaching and type of the management and found no significant in locality of the institution. There is a positive, significant correlation between the profession perception and profession commitments of geography teachers.